CP Violation: Differing Binding Energy Levels of Quarks and Antiquarks, and Their Transitions in Λ-Baryons and B-Mesons - Dimitris M. Christodoulou; Demosthenes Kazanas (Foundations)
We consider spontaneous quark transitions between the <semantics>Λ0</semantics> baryon and its resonant states, and (anti)quark transitions between the neutral kaon K0 and the two heavy <semantics>ηq</semantics>-mesons (q = c, b). The measured differences in mass deficits are used to calculate the binding energy levels of valence c and b (anti)quarks in these transitions. The method takes into account the isospin energy release in K0 transitions and the work conducted by the strong force in suppressing internal Coulomb repulsions that develop in the charged <semantics><msubsup>Λc+</msubsup></semantics>-baryon. We find that the flips <semantics>s→c</semantics> and <semantics><mover>s¯</mover>→<mover>c¯</mover></semantics> both release energy back to the strong field and that the overall range of quark energy levels above their u-ground is 100-MeV wider than that of antiquark energy levels above their <semantics><mover>d¯</mover></semantics>-ground. The wider quark range stems from the flip <semantics>s→b</semantics>, which costs 283 MeV more (or <semantics>3×</semantics> more) than the corresponding antiquark flip <semantics><mover>s¯</mover>→<mover>b¯</mover></semantics>. At the same time, transitions from the respective ground states to the s and <semantics><mover>s¯</mover></semantics> states (or the c and <semantics><mover>c¯</mover></semantics> states) point to a clear origin of the elusive charge-parity (CP) violation. The determined binding energy levels of (anti)quarks allow us to analyze in depth the (anti)quark transitions in <semantics>Λ</semantics>-baryons and B-mesons.